A study on fragmentation behavior, inorganic melt phase formation, and carbon loss during high temperature gasification of mineral matter rich fraction of Pittsburgh No. 8 coal. (15th November 2017) - Krishnamoorthy, Vijayaragavan; Tchapda, Aime H.; Pisupati, Sarma V.
Highlights: Ash fragmentation to finer size is limited irrespective of particle sizes. Mineral matter rich fraction forms melt phase at lower conversion (<30%). Encapsulation of organic matter by melt phase leads to unburnt carbon for both the particle sizes. Abstract: Computational models are being developed to determine the fate of organic and inorganic matter during gasification to improve operational reliability and carbon conversion in entrained flow gasifiers. Current models being developed to simulate entrained flow gasifiers assume homogeneity of the coal phase. However, coal is not homogeneous, and various size and density fractions behave differently during gasification. Therefore, a more accurate model can be developed by determining the behavior of various size and density fractions of coal. From that perspective, two particle size distributions (75–106 µm and 212–425 µm) of the mineral matter rich fraction of Pittsburgh No. 8 coal obtained using the float and sink method were gasified in a laboratory-scale entrained flow reactor at 1773 K. Char-ash particles from the two size fractions were characterized using Scanning Electron Microscope-Energy Dispersive X-ray Spectroscopy (SEM-EDS), X-ray Diffraction (XRD), Mossbauer spectroscopy, thermogravimetric analysis, and a micro-sifter for particle size distribution (PSD). The char-ash sample derived from the coarser-sized fraction (212–425 µm) showed limited fragmentation (∼8%), while the finer-sized fraction showed no fragmentation. On the other hand, agglomerates were seen for both the particle size fractions with the finer-sized fraction having more melt phase and agglomerates than the coarser-sized fraction. The melt phase composition in the agglomerates is linked to the presence Fe 2+ -glass and fayalite for both the particle size fractions. The data also confirm that the mineral matter rich particles form melt phase and initiate slagging in the gasifier even at a lower conversion level (<30%). The melt phase thus formed covers the carbonaceous matter in the particle and contributes substantially to the unburnt carbon in the slag.